Hubungan Kejadian Pada Perundungan (bullying) Dengan Dampak Psikologis Mahasiswa Di Lingkungan Universitas Islam Sultan Agung Semarang - Nur Makhmudah; Setyo Trisnadi (Jurnal Riset Multidisiplin Edukasi, 2026)
Bullying in higher education is a serious issue that impacts students' mental health. This study aims to analyze the relationship between bullying incidents and psychological impacts in the form of stress, anxiety, and depression in students of the Faculty of General Medicine, Sultan Agung Islamic University, Semarang. This study design uses a quantitative approach with an observational analytical cross-sectional design technique. A total of 96 samples were from students of the Faculty of General Medicine, Unissula, in the 2024/2025 academic year. Data were collected through the Olweus  bullying questionnaire to measure the level of  bullying incidents and the Depression Anxiety Stress Scale (DASS-Y) to assess the level of stress, anxiety, and depression using. Data regarding student identity, such as age, gender, and year, were obtained through information entered in the inform consent on Google Form. Analysis of data on the relationship with stress levels and sleep quality was carried out descriptively using the One-Sample Kolmogorov-Smirnov Test. The results showed that 74% of respondents experienced moderate  bullying, 4.3% experienced moderate depression, 53.1% experienced moderate anxiety, and 47.9% experienced moderate stress. Female respondents reported more psychological impacts than male respondents. Bivariate analysis showed a significant relationship between  bullying incidents and the psychological impacts experienced by students. It can be concluded that  bullying has a significant psychological impact on students, particularly in the form of stress, anxiety, and depression.